2002
DOI: 10.1002/jbm.10140
|View full text |Cite
|
Sign up to set email alerts
|

Stress influence on interface in plasma‐sprayed hydroxyapatite coatings on titanium alloy

Abstract: During clinical use of hydroxyapatite-coated implants, mechanical stresses are added to pre-existing residual stresses. The magnitude of these stresses affects the coating's performance. In this work we studied, by neutron diffraction and conventional X-ray diffraction methods, the macrostresses induced by a plasma-spraying process in the coating and at the interface. Neutron diffraction is one of the most suitable techniques for studying the strain distribution in a bulk material. X-ray diffraction was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Brown et al calculated the residual stress by adopting an unspecified Young's modulus. 40 The Young's modulus for the residual stress calculation by the XRD sin 2 method was not mentioned by Millet et al 41 Han et al employed the hole-drilling method to measure the residual stress in plasma-sprayed HA, 19 in which an apparently estimated Young's modulus of 81 GPa was used to calculate the residual stress in the coating (Table IV).…”
Section: Young's Modulus Of Bulk Hydroxyapatite and Hacsmentioning
confidence: 99%
“…Brown et al calculated the residual stress by adopting an unspecified Young's modulus. 40 The Young's modulus for the residual stress calculation by the XRD sin 2 method was not mentioned by Millet et al 41 Han et al employed the hole-drilling method to measure the residual stress in plasma-sprayed HA, 19 in which an apparently estimated Young's modulus of 81 GPa was used to calculate the residual stress in the coating (Table IV).…”
Section: Young's Modulus Of Bulk Hydroxyapatite and Hacsmentioning
confidence: 99%
“…On the other hand, smaller secondary cooling in HVOF system arises from the lower temperature in this coating technique, and the main cause of tensile residual stress in HVOF system is the high velocity, which produces great primary cooling (see Table ). Some investigators have reported tensile residual stress of HA‐APS coatings, while others have found it compressive residual stress . A group of investigators have reported low values of residual stress in plasma spraying with values between 20 to 40 MPa, while others have reported much greater values, that is, 200–450 MPa .…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators 38,55 have reported tensile residual stress of HA-APS coatings, while others have found it compressive residual stress. 21,25,56 A group of investigators have reported low values of residual stress in plasma spraying with values between 20 to 40 MPa, 38 while others have reported much greater values, that is, 200-450 MPa. 55 Although high residual stress coatings have shown to offer poor mechanical stability in in-vivo condition, 21 however the positive or negative influence of residual stress in in-vivo conditions is not known yet.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxyapatite (HA) coatings, especially plasma-sprayed coatings on metallic substrate, is believed to combine the bioactivity of HA and the strength of the metal. [1][2][3][4][5][6]. However, due to huge differences in Yong's modulus, hardness and thermal expansion coefficients between the HA and the metallic substrates, large residual stress maybe arise at the ceramic/metal interface, which often causes a lot of cracks in the coatings or separates the ceramic coatings from the metallic substrate.…”
Section: Introductionmentioning
confidence: 99%